(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Children with malignancy who are under treatment with nephrotoxic drugs are at risk of renal dysfunction. Due to increased life expectancy, evaluation of drug toxicity is now of higher importance than before. The aim of this study is to compare two methods of GFR measurement. Methods. An analytical study on children with malignancy undergoing chemotherapy with nephrotoxic drugs (cisplatin, carboplatin, cyclophosphamide, ifosfamind, etoposide) during 2016 and 2017 in Mofid Children Hospital was done. Demographic information, anthropometric measurements, type of malignancy, type of chemotherapy medication and also lab tests including CBC and the biochemistry indices were recorded. The GFR of each patient was calculated using Schwartz formula and DTPA scanning. The rates were compared and the difference was analyzed statistically. Results. According to Schwartz formula, 24% of patients needed dose adjustment, while based on DTPA scanning, this rate was 6%. Comparing these two measures by paired T-test, showed a significant statistical difference (P < .05). Schwartz formula had 25.5% more positive results of predicting the need for dose adjustment. The two measured GFRs for each person were evaluated in terms of compatibility and correlation based on Kappa statistical method, which were incompatible and had significant difference (P < .05). Conclusion. Using evaluative methods including Schwartz formula cannot demonstrate renal dysfunctions reliability in patients taking nephrotoxic chemotherapy drugs. Eventually if the GFR measurement method overestimates patients with renal dysfunction, the patients will not be able to make adequate use of the therapeutic effects of chemotherapy with the appropriate dosage.